Vegetation association at montane forests in Cameron Highland, Pahang, Malaysia - Rohaizat, Haziq Syahmi (2018)
The study was done in primary montane forest area of Cameron Highland to obtain the information particularly the vegetation type, coverage and abundance of flora in that area. Two forest areas namely Sungai Terla and Batu Gangan Forest Reserve, Cameron Highland, Pahang that located at elevation of 1300 m and above from sea level chosen. The work principle and concept of vegetation science in which plants will be treated as several communities and analysed using matrix table to classify plant community. A total of ten plots and 345 species of plants were recorded. Mostly, these species were known as intermediate The characteristic of the whole group of plots were represented by the species with high constancy, while those species which have very low constancy were most probably not included in the characteristic groups of plots and the last one is the Differentiated table which is to rearranging the plots based on the new sequence. At the same time, the species in every group of associated species were arranged based on descending order which were from high constancy. The second ordinated partial table might be constructed to avoid confusion due to the existence of many plots. The final differentiated table will display the plots which contain species that have been arranged according to their particular associations. Field studies have released output on the richness of montane forest species in the Sungai Terla B Forest Reserve and the Batu Ganggan Forest Reserve in Cameron Highland, Pahang, Malaysia. Among the species recorded in all the inventory plots have shown the richness of the community species of montane forest in Cameron Highland. The dominant species of montane forest are Selaginella willdenowii – Engelhardtia roxburghiana. Due to this community group has shown that this community plays an important role in the forest stratum that inhabit the surface of the forest that can affect the growth of other septic plants, thus contributing to the species of animals inhabiting the area. Percentage rates of vegetation in this mountain forest can be clearly seen when the sub-community growth that is backed up to this mountain forest, Lindera pipericarpa - Syzygium javanicum and Syzygium javanicum - Carallia euginioides. In addition, this density of fertility can also be seen when a species of trees with different canopy sizes varies from one another.